Antineuronal antibodies in idiopathic achalasia and gastro-oesophageal reflux disease. Issue 5 (1st May 2003) - Moses, P L; Ellis, L M; Anees, M R; Ho, W; Rothstein, R I; Meddings, J B; Sharkey, K A; Mawe, G M
Abstract : Background and aims: The precise aetiology of achalasia is unknown although autoimmunity has been implicated and is supported by several studies. We screened sera from patients with achalasia or gastro-oesophageal reflux disease (GORD) to test for circulating antimyenteric neuronal antibodies. Methods: Serum was obtained from 45 individuals with achalasia, 16 with GORD, and 22 normal controls. Serum was used in immunohistochemistry to label whole mount preparations of ileum and oesophagus of the guinea pig and mouse. Also, sections of superior cervical and dorsal root ganglia, and spinal cord were examined. Results: Positive immunostaining of the myenteric plexus was detected in significantly more achalasia and GORD samples than control samples (achalasia, p<0.001; GORD, p<0.01), and immunoreactivity was significantly more intense with achalasia and GORD serum samples than controls (achalasia, p<0.01; GORD, p<0.05). There was no correlation between intensity of immunoreactivity and duration of achalasia symptoms. In most cases, achalasia and GORD sera stained all ileal submucosal and myenteric neurones, and oesophageal neurones. Immunostaining was not species specific; however, immunostaining was largely specific for enteric neurones. Western blot analysis failed to reveal specific myenteric neuronal proteins that were labelled by antibodies in achalasia or GORD serum. Conclusions: These data suggest that antineuronal antibodies are generated in response to tissue damage or some other secondary phenomenon in achalasia and GORD. We conclude that antineuronal antibodies found in the serum of patients with achalasia represent an epiphenomenon and not a causative factor.